2004
DOI: 10.1007/s00134-004-2310-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric outcome following paediatric intensive care unit (PICU) admission: a cohort study

Abstract: Post traumatic stress disorder diagnosis and symptomatology is significantly more common in families where a child has been admitted to the PICU. Consideration should be given to providing psychological support for children and parents after PICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
179
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(194 citation statements)
references
References 25 publications
10
179
1
4
Order By: Relevance
“…A group of 35 children, and their parents, who had been hospitalized in a pediatric ICU were compared with 33 children/parent pairs who had been hospitalized on general pediatric wards; 21% of pediatric ICU-discharged children developed PTSD compared with none of the ward admissions. Pediatric ICU children had significantly more PTSD features of irritability and persistent avoidance of reminders of the admission [13]. In another study, 22% of 143 children 7 to 15 years old who experienced motor vehicle injury met criteria for PTSD.…”
Section: Epidemiology Of Post-traumatic Stress Symptoms In Pediatric mentioning
confidence: 93%
See 1 more Smart Citation
“…A group of 35 children, and their parents, who had been hospitalized in a pediatric ICU were compared with 33 children/parent pairs who had been hospitalized on general pediatric wards; 21% of pediatric ICU-discharged children developed PTSD compared with none of the ward admissions. Pediatric ICU children had significantly more PTSD features of irritability and persistent avoidance of reminders of the admission [13]. In another study, 22% of 143 children 7 to 15 years old who experienced motor vehicle injury met criteria for PTSD.…”
Section: Epidemiology Of Post-traumatic Stress Symptoms In Pediatric mentioning
confidence: 93%
“…At follow-up 2 months later with 161 of the parents, 21% met symptom criteria for PTSD [16]. A British study found that parents of children hospitalized in the ICU were more likely to screen positive for PTSD (27%) compared with parents of children admitted to the ward (7%) [13]. In another study of mothers of children experiencing acute life-threatening illness, 111 mothers of children who survived hematopoietic stem cell transplantation completed self-report measures of psychological functioning at the time of hematopoietic stem cell transplantation and self-report measures and a structured psychiatric interview 18 months later.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…* The authors of several cohort-comparison studies attempted to elucidate the difference between family impact in life-threatening and non-life-threatening disease states. 31,41,71,73,74 Sample sizes varied markedly (range: 7-189 families), and many were anecdotal. Most studies described findings in cohorts that were largely white and excluded non-English-speaking families.…”
Section: Impact On Families Of Critically Ill Childrenmentioning
confidence: 99%
“…This limitation is a crucial deficit and vital to note when planning future research. In addition, most family-impact data have been obtained from mothers, 12,63,67,69,71,74,75 although one study was conducted solely with fathers. 31 A substantial number of studies have focused on children who were in the PICU for the first time.…”
Section: Impact On Families Of Critically Ill Childrenmentioning
confidence: 99%
See 1 more Smart Citation